Iraqi Digital Art: Origin and Evolution - Sanaa Mohsin (Iraqi Journal of Science, 2021)
The current challenge facing our age is the information digitization, at the same time, there is a huge development in the interdisciplinary of technologies with sciences. In the last few years, the World witnessed a number of information challenges with different dimensions, including digital dimensions, which are called the digital world and the virtual world for authors and movie writers. Consequently, the digital art concept emerged that utilizes the computer in an efficient way and as a new technique for drawing. This art is considered a great leap for modern art. The influence of digital technology transformed traditional arts like painting and sculpture into new forms, from pure arts to virtual reality. The most important characteristics and advantages are reflected in saving time, effort, cost and area. Digitally, art would enrich Iraqi culture by employing Iraqi creativity. This paper targets the concept of digital art, characteristics of art in virtual society and presenting the history – origins and evolution – of digital art. A group of paintings have been created using Photoshop Cc, Photo Shop C5 and Art Rage programs.